A structured catalyst support combining electrochemically exfoliated graphene oxide and carbon black for enhanced performance and durability in low-temperature hydrogen fuel cells. (1st July 2021) - Ji, Zhaoqi; Perez-Page, Maria; Chen, Jianuo; Rodriguez, Romeo Gonzalez; Cai, Rongsheng; Haigh, Sarah J.; Holmes, Stuart M.
Abstract: Reduced electrochemically exfoliated graphene oxide (rEGO) is combined with carbon black (CB) as a hybrid support material to improve platinum (Pt) catalyst electrochemical activity and durability. Pt/rEGO2 -CB3 (rEGO/CB ratio 2/3) retains 71% of initial electrochemical surface area (ECSA) and maintains higher oxygen reduction reaction (ORR) activity compared to Pt/CB after 30000 cycles of the accelerated stress test (AST). In addition, Pt/rEGO2 -CB3 shows a 1.8 times improvement in the hydrogen fuel cell performance compared with Pt/CB and is more stable after 24 h at a continuous 0.60 V. The Pt/rEGO2 -CB3 promotes the 4e − reaction pathway demonstrated by linear sweep voltammetry (LSV), which leads to greater ORR activity. In addition, the combination of rEGO and CB leads to both enhanced transport properties and improved stability. The Pt particles on both CB and rEGO are less likely to agglomerate in the composite support than in either of the two carbon supports when used alone. Graphical abstract: Pt supported on a hybrid support combining electrochemically exfoliated graphene oxide and carbon black (Pt/rEGO2 -CB3 ) achieved 1.8 times improved performance and higher durability compared with Pt supported on a single carbon black (Pt/CB). Image 1 Highlights: Nano-sized graphene oxide were prepared by electrochemical exfoliation method. The structured support combining EGO and carbon black relieves mass transfer issue. Pt/rEGO2 -CB3 significantly improves PEMFC performance with high durability.